HUBUNGAN PELAYANAN PRIMA (EXCELLENT SERVICE) PERAWAT DENGAN KEPUASAN PASIEN - M.Kes, Zuryati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2085)
Satisfaction is the feeling that arises in the patient when the service has exceededexpectations. Based on preliminary study conducted on March 14, 2017 it was found that thelevel of patient satisfaction in the category enough as many as 6 (60%) respondents. Thepurpose of this study was analyzed the relation excellent service nurse to the patientsatisfaction in Intensif Care Unit RSUD Syarifah Ambami Rato Ebu Bangkalan.The design of this study was analytic corelative using a ?Cross sectional?. The studypopulation was all patiens treated in the Intensif Care Unit RSUD Syarifah Ambami RatoEbu Bangkalan. The sample was 23 respondents. The sample used non-probability samplingby quota sampling. Independent variables was excellent service nurse and dependentvariables is satisfaction patient. The collected data used a questionnare then it was analyzedby Spearman Rank with ? = 0,005.The results showed June, 2017 that nurses who did good excellent service and satisfiedpatient by 8 (34,8%) respondents, and performed excellent service nurse less and patientswere unsatisfied as much as 1 (4,3%) respondent. Spearman rank statistical test showed that?value =0,042 < ?=0,05 which mean there was a relation between excellent service nurse tothe patient satisfaction in Intensive Care Unit RSUD Syarifah Ambami Rato Ebu Bangkalan.For health workers, especially nurses to pay more attention and understand about theexcellent service that refers to patient satisfaction. So, the patient can recover from his illnesthanks to the encouragement and support of the nurse and is statisfied with the serviceprovided by the nurse.